2021
DOI: 10.3892/etm.2021.10441
|View full text |Cite
|
Sign up to set email alerts
|

DL‑3‑n‑butylphthalide protects H9c2 cardiomyoblasts from ischemia/reperfusion injury by regulating HSP70 expression via PI3K/AKT pathway activation

Abstract: DL-3-n-butylphthalide (NBP) is commonly used to treat ischemic strokes due to its antioxidative and anti-inflammatory effects. The present study aimed to examine the protective effects of NBP on myocardial ischemia-reperfusion injury (MIRI) by establishing a MIRI model in H9c2 cells. Cell viability assay using Cell Counting Kit-8, lactate dehydrogenase (LDH) cytotoxicity and lipid peroxidation malondialdehyde (MDA) content were assessed to detect cell activity, degree of cell injury and oxidative stress reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Guo et al [ 19 ] found that matrine could protect cardiomyocytes from IRI by activating the JAK2/STAT3 pathway to upregulated HSP70 expression. Yu et al [ 20 ] similarly showed that DL-3-n-butylphthalide protects H9c2 cardiomyocytes from ischemia/reperfusion injury by increasing the HSP70 expression through activation of the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [ 19 ] found that matrine could protect cardiomyocytes from IRI by activating the JAK2/STAT3 pathway to upregulated HSP70 expression. Yu et al [ 20 ] similarly showed that DL-3-n-butylphthalide protects H9c2 cardiomyocytes from ischemia/reperfusion injury by increasing the HSP70 expression through activation of the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%